Association of Pain Location and Lidocaine Dosage with Clinical Response to Targeted Intramuscular Lidocaine Injection in Diabetic Neuropathic Pain - Wiradinata, Harsono; Roethmia Yaniari; I Made Subhawa Harsa; Atik Sri Wulandari; Pratika Yuhyi Hernanda (Universitas Wijaya Kusuma Surabaya, 2026)
Background: Diabetic neuropathic pain (DNP) is often refractory to oral analgesics. It is a complication of diabetes mellitus that causes sensory disturbances. Oral pharmacological therapies, including antidepressants, anticonvulsants, and opioids, often have limited efficacy and may cause systemic adverse effects. Objective: This prospective observational cohort study evaluated whether anatomical pain location and lidocaine dose predict the short-term analgesic response to targeted intramuscular lidocaine injection at the patient’s site of maximal pain in patients with diabetic neuropathic pain. Methods: Thirty-one adults with DNP treated at Bhayangkara Hospital were enrolled. They received 1% plain lidocaine at doses of 3, 4, or 5 mg/kg, administered intramuscularly at the site of maximal pain. Pain intensity was assessed at baseline and at 30 minutes, 1, 2, 4, and 6 hours after injection using the Visual Analog Scale (VAS) and the Neuropathic Pain Symptom Inventory (NPSI). Result: The results showed a dose-dependent decrease in mean VAS scores, and this dose-response trend was statistically significant (ANOVA, p = 0.018). The composite NPSI score decreased by an average of 34.2%. Furthermore, patients with dorsal foot pain and those experiencing electric shock/paresthesia sensory phenotypes showed the greatest reductions in pain scores. Conclusion: These findings indicate that targeted IM lidocaine produced rapid short-term analgesia within 30 minutes, lasting approximately 4 to 6 hours. Anatomical targeting and dose selection may influence analgesic outcomes and may support individualized, symptom-directed strategies for managing diabetic neuropathic pain.